2015
DOI: 10.1371/journal.pone.0134501
|View full text |Cite
|
Sign up to set email alerts
|

Control of a Supernumerary Robotic Hand by Foot: An Experimental Study in Virtual Reality

Abstract: In the operational theater, the surgical team could highly benefit from a robotic supplementary hand under the surgeon’s full control. The surgeon may so become more autonomous; this may reduce communication errors with the assistants and take over difficult tasks such as holding tools without tremor. In this paper, we therefore examine the possibility to control a third robotic hand with one foot’s movements. Three experiments in virtual reality were designed to assess the feasibility of this control strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 37 publications
2
41
0
Order By: Relevance
“…Carrozza et al, 2007;Abdi et al, 2015;Dougherty and Winck, 2019). Abdi et al (2015) study the control of a third robotic hand via the foot in virtual reality, for robotic surgery applications, showing similar learning trends to what we observe here. Results obtained with adaptive foot interfaces for robot control (e.g.…”
Section: Discussionsupporting
confidence: 77%
“…Carrozza et al, 2007;Abdi et al, 2015;Dougherty and Winck, 2019). Abdi et al (2015) study the control of a third robotic hand via the foot in virtual reality, for robotic surgery applications, showing similar learning trends to what we observe here. Results obtained with adaptive foot interfaces for robot control (e.g.…”
Section: Discussionsupporting
confidence: 77%
“…Two minutes of practice was not enough for developing the sense of ownership towards the third hand. In our previous experiment with three different virtual games 35 , we observed that the sense of ownership towards the third hand improved constantly through the games. Also, performing different types of three handed tasks may enhance the ownership.…”
Section: Discussionmentioning
confidence: 85%
“…The feeling of an independent supernumerary limb has been presented in a medical case study [8], but recent advances in robotics and computer science suggest that artificial supernumerary limbs could be incorporated into healthy human function in the future. Supernumerary robotic limbs can be built to assist human movements [9,10] and brain-computer interfaces have been shown to work during concurrent movement execution [11]. It is therefore important to understand if the brain is capable of feeling ownership over additional and independent supernumerary limbs and agency over their actions.…”
Section: Introductionmentioning
confidence: 99%